(untitled) (Gaceta Técnica, 2022)
Industrial buildings are structures for various uses in the trade or development of a certain population, consequently, these types of structures are in high demand in the field of civil engineering, especially in the area of design and construction; For this reason, this research presents an analysis of self-supporting circular-type roofs, applying the finite element method under the help of the ANSYS Workbench 19.0 simulation software using first-order area-type finite elements. The vertical deformations obtained by original cross sections were compared to with the deformations of an equivalent cross section in inertia and weight. Industrial buildings with lights of 10, 20, 30, and 40 m were analyzed. A self-supporting roof section type CS 1000-610, material ASTM 653 of SS40 base metal and galvanized coating by galvanizing Z275 (G90) was considered. The support structure is made up of metal structure truss-type beams and columns in accordance with the LRFD methodology and the NEC 2015, AISI S100-07, AISC341-05 standards. Additionally, support plates suitable for this type of roof were analyzed. Stress concentrations were observed in the region of the support plate, deformations by original sections greater than the deformations by equivalent sections, and variations in cover weight and live load, the latter having a variation between 14,75% to 29,14%.